PENGARUH KEPERCAYAAN, KEAMANAN, DAN KEMUDAHAN PENGGUNAAN APLIKASI TERHADAP MINAT BELI ULANG (STUDI KASUS DI E-COMMERCE JD.ID) - Saripudin Saripudin; Nabilla Faihaputri (JURNAL ILMIAH EDUNOMIKA, 2021)
The use of the internet not only for communication and finding information, but also for online transaction. One of e-commerce that is developing in Indonesia is JD.id. However, Indonesian people's interest in JD.id is still relatively low, where in Q2 2020 JD.id was ranked sixth, which means JD.id is still not the main choice of Indonesian people in using e-commerce. The purpose of this study is to find out and analyze how much effect of trust, security and ease of use of the application have on repurchase interest in JD.id. The sample in this study were 100 consumers who had used JD.id determined by purposive sampling technique. This research is a quantitative research with survey method, where this research is causal associative. The method of data collection in this research is using the method of distributing questionnaires through social media. The data analysis technique used in this research is path analysis using the SmartPLS 3.0 program. The results of the study found that trust, security and ease of use of the application partially and simultaneously had a significant positive effect on repurchase interest in JD.ID.